Kegiatan Marketing Public Relations PT. X Bandung pada Program “Komunitas Siap Gerak” - Nidiya Regika Putri; Mohamad Subur Drajat (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Currently, there are many young, beautiful and accomplished Muslim designers who make modern clothing without leaving Islamic law. The purpose of this research is to find out the management of Marketing Public Relations activities, optimization of the media used and the reasons for PT. X Bandung chose the “Ready to Move Community” Program. The theory used is, three ways strategy, new media, and the operational concept of public relations. This research was structured using a qualitative method with a case study approach. Meanwhile, the data collection technique was done by interview, observation, literature study and documentation. The results of this study found that in program management, namely determining goals, time & activities carried out, determining the target public, then collaborating with professional trainers, strategies to attract consumer interest and the results of the